The Influence of Principal Leadership and Work Motivation on Teacher Performance at SMK Negeri 1 OKU - Yurida; Arafat, Yasir; Destiniar (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The purpose of this study was to analyze the effect of principal leadership and work motivation on teacher performance at SMK Negeri 1 OKU. The research method used in this research is quantitative method. The population in this study were 62 teachers who were taken as the research sample, so this research is called population research. The data collection techniques used were questionnaires and documentation. The data analysis technique used is the prerequisite test, which includes the normality test, linearity test, autocorrelation test, multicollinearity test and heteroscedasticity test. Analysis testing using partial test (t-test) and simultaneous test (F-test). Based on the research results, it is obtained data that the principal's leadership and work motivation jointly affect the performance of teachers at SMK Negeri 1 OKU.